2020
DOI: 10.1039/d0ra02951c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zn doping on phase transition and electronic structures of Heusler-type Pd2Cr-based alloys: from normal to all-d-metal Heusler

Abstract: By first-principles calculations, for Heusler alloys Pd2CrZ (Z = Al, Ga, In, Tl, Si, Sn, P, As, Sb, Bi, Se, Te, Zn), the effect of Zn doping on their phase transition and electronic structure has been studied in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…526 Depending on the relative electronegativity of the X and Y elements, the empirical Burch's rule states that the inverse Heusler structure is preferred if the valence of Y is larger than that of X, e.g., Y is to the right of X if they are in the same row of the periodic table. 527 Several HTP calculations have been done to assess the Burch's rule, such as in Sc- 528 and Pd-based 529,530 Heuslers. Additionally, the nonmagnetic L2 1 Heusler compounds as high-strength alloys 531 thermoelectric 532 materials have been studied.…”
Section: B Heusler Compoundsmentioning
confidence: 99%
“…526 Depending on the relative electronegativity of the X and Y elements, the empirical Burch's rule states that the inverse Heusler structure is preferred if the valence of Y is larger than that of X, e.g., Y is to the right of X if they are in the same row of the periodic table. 527 Several HTP calculations have been done to assess the Burch's rule, such as in Sc- 528 and Pd-based 529,530 Heuslers. Additionally, the nonmagnetic L2 1 Heusler compounds as high-strength alloys 531 thermoelectric 532 materials have been studied.…”
Section: B Heusler Compoundsmentioning
confidence: 99%
“…For the cases above, the Mn(D) carries most of the magnetic moment, and the Mn(D)− Mn(D) coupling is expected to result in FM ordering since the interatomic distance is identical with the Mn(B)−Mn(B) interatomic distance for an L2 1 structure (see Figure 2b). Moreover, Wang et al 82 studied the role of the Zn transition metal on the electronic structure and phase transition of Pd 2 CrZ (Z = Al, Ga, In, Tl, Si, Sn, P, As, Sb, Bi, Se, Te, Zn) systems. For the case Z = Zn, the study revealed that the Pd 2 CrZn all-d-metal composition, has an energetically stable L2 1 structure with Zn (3d 10 4s 2 ) atoms occupying the (D) site.…”
Section: All-d-metal Heusler Alloys: Recentmentioning
confidence: 99%
“…Moreover, Wang et al studied the role of the Zn transition metal on the electronic structure and phase transition of Pd 2 CrZ (Z = Al, Ga, In, Tl, Si, Sn, P, As, Sb, Bi, Se, Te, Zn) systems. For the case Z = Zn, the study revealed that the Pd 2 CrZn all- d -metal composition, has an energetically stable L2 1 structure with Zn (3 d 10 4 s 2 ) atoms occupying the (D) site.…”
Section: All-d-metal Heusler Alloys: Recent Findingsmentioning
confidence: 99%
“…Later, a series of other shape memory alloys (SMAs) were manufactured such as Cu-based alloys (Cu-Zn, Cu-Sn), Ni-based alloys (Ni-Ti, Ni-Al), Fe-based alloys (Fe-Pd, Fe-Pt) . However, the most commonly used SMAs are nitinol alloys (Ni-Ti) and Heusler alloys (Cu-Ni-Al, Ni-Mn-Ga) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Recently, the SME has been observed on some high entropy alloys (HEAs) such as Ti-Ta-Hf-Nb-Zr, Fe-Ni-Co-Al-Ti, Ti-Zr-Co-Ni-Cu.…”
Section: Introductionmentioning
confidence: 99%
“…The SME in Cu-Al-Mn Heusler alloys was first published in 1996 [22]. The superelasticity (SE) of these alloys is improved through controlling structure and particle size [23][24][25][26][27][28][29][30][31]. So far, the superelastic property of these alloys has reached the level of Ni-Ti ones.…”
Section: Introductionmentioning
confidence: 99%